Seasonal patterns of vegetation drought resilience and vegetation loss in Central Asia - Liangliang Jiang; Guangming Wu; Xinyuan Gui; Xiaoran Liu (PLoS ONE, 2026)
Drought events have become increasingly common in Central Asia, increasing the risk of vegetation degradation. In this study, the resilience of vegetation to drought and its drivers was investigated across different seasons. The findings revealed that western Central Asia faced a notably high incidence of spring droughts, characterized by longer durations and greater severity than droughts in other seasons. In contrast, the Aral Sea Basin experienced fewer droughts in summer and autumn, although these droughts were more severe and intense and had longer durations. Croplands, particularly those in northern Kazakhstan, generally demonstrated relatively low resistance but relatively strong resilience. In contrast, sparsely vegetated areas in regions such as southern Xinjiang and areas downstream of the Aral Sea Basin presented high drought resistance but relatively low resilience. Precipitation and vapour pressure deficit (VPD) had the most significant impact on drought resilience in Central Asia, with a combined contribution of 55.18%, particularly in the northern and eastern regions of the area. The vegetation in spring was characterized by the highest resistance and resilience levels (40.67% and 40.65%, respectively) in Central Asia, followed by those in summer. In terms of vegetation loss, vegetation in spring accounted for the greatest proportion (44.03%), followed by that in summer, at 31.07%. The main characteristics of drought (duration and intensity) were the major factors influencing the loss of vegetation, especially in grasslands and sparsely vegetated areas. During prolonged summer droughts (>40 months), grasslands and sparse vegetation suffered substantial declines in gross primary productivity (GPP). In contrast, forests exhibited more severe GPP reduction at a drought peak of around 2 and intensity above 1.5. Quantifying the resilience and loss of vegetation to drought across different seasons can aid in the formulation of effective strategies to prevent and manage vegetation degradation in Central Asia.